CTA Project Completion Report: ActionAid Haiti - AAH - Visser, Piet; Reid, Robert (Technical Centre for Agricultural and Rural Cooperation, 2020)
In early 2018, Action Aid Haiti (AAH) approached the Technical Centre for Agricultural and Rural Cooperation (CTA), to collaborate in a project that in the context of climate change, would promote the production of environmentally sustainable crops, and reduce the vulnerability of persons particularly women in rural communities. CTA, based on its mandate and strategic plan for the Caribbean region, agreed to this collaboration. Hence the genesis to this 15-month cost-sharing project entitled ‘Supporting small-holders and mostly women in sustainable production and marketing of tubers, through innovative techniques at all value-chain levels, Haiti, Grand’Anse region (ActionAid Haiti - AAH).